Peningkatan hasil belajar matematika siswa dengan strategi “pasangan belajar bersama” - Rohmad, Ali; Kuswidi, Iwan (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2024)
Student proficiency in mathematics, as reflected in learning outcomes, remains a challenge that requires solutions. This study aimed to improve students' mathematics learning outcomes through the application of the "Collaborative Learning Pairs" strategy. The research method employed was Classroom Action Research (CAR), which included cycles of planning, action, observation, and reflection to evaluate the effectiveness of the applied strategy. The "Collaborative Learning Pairs" strategy was an adaptation of the cooperative learning model Think-Pair-Share, which formed learning pairs based on students' abilities, proximity of their homes, gender, and familiarity with each other. The data for this study were students' learning outcomes on flat and solid geometry topics. The research subjects were 28 seventh-grade students from SMP Negeri 4 Geyer Grobogan during the even semester of the 2022/2023 academic year. Data were collected through tests and observations. The data analysis included descriptive statistics, followed by a comparison with the research success criteria. The findings indicated that the strategy involved stages of student pairing, planning classroom and home activities, implementation, and evaluation. The data analysis results showed that before the strategy implementation (Pre-Cycle), the average mathematics score was 70.5, with only 28.57% of students achieving mastery with a Minimum Passing Criteria (KKM) of 80. In Cycle 1, after applying the strategy, the average score increased to 82.39, with 64.28% of students achieving mastery. In Cycle 2, the average score further increased to 85.32, with 78.57% of students achieving mastery. The results demonstrated that the "Collaborative Learning Pairs" strategy effectively improved students' mathematics learning outcomes. The significant increase in both average scores and the percentage of students achieving mastery from the Pre-Cycle to Cycle 2 indicated that this strategy was a viable solution for addressing the challenges in students' mathematics proficiency